(untitled) (Research, Society and Development, 2021)
Acne vulgaris is a chronic dermatosis of the pilosebaceous follicle, which has, as fundamental factors, sebaceous hyperproduction. There is no universal epidemiological profile for it. It affects both genders and is a public health problem. The objective of this work was to evaluate the effectiveness of the treatment of Chamomile gel (Matricaria chamomilla L.) associated with low frequency Red LED (4.82 – 3.84Hz) in the treatment of Acne Vulgaris. This is an experimental field study with a quanti-qualitative approach including 20 female patients seen at a Dermatofunctional Physical Therapy clinic in the city of Floriano-PI. Patients were divided into groups of five women each. To assess the condition of the skin, the Visual Facial Perception Scale - EVPF and the assessment by Counting the Number of Lesions - CNL were used. At the end of the study, it was found that the treatment of acne using 5% chamomile gel associated with a low-frequency Red LED device (4.82 - 3.84Hz), proved to be effective in reducing the inflammatory process of the skin. Presenting itself as a safe, accessible and effective therapy. Other special skin care is also important for patients with this dermatological condition.